Illocutionary Speech Acts of the Devil Character in the Dialogue of the Animated Film Adam and the Devil on YouTube One Way Production - Marisa Hasna Kaamilah; Nurlinah; Maman Abdul Djalil (Raja Zulkarnain Education Foundation, 2026)
The research on illocutionary speech acts of the Devil character in the dialogue of the animated film Adam and the Devil on YouTube One Way Production contains various aspects of the meaning of speech acts from each dialogue, especially in the Devil character. This study aims to describe: 1) the types of illocutionary speech acts in the dialogue of the animated film Adam and the Devil; 2) the function of illocutionary speech acts in the dialogue of the animated film Adam and the Devil. This study uses John R. Searle's theory which classifies illocutionary speech acts into 5 types, namely; assertive, expressive, directive, commissive, and declarative illocutionary. The method used in this study is descriptive qualitative with the technique of listening and noting in data collection, and the pragmatic matching method in data analysis based on time triangulation. This study produced 309 data types of illocutionary speech acts with a description of 126 assertive illocutionary data, 58 expressive illocutionary data, 117 directive illocutionary data, 8 commissive illocutionary data. Meanwhile, in the devil's dialogue in the animated film Adam and Iblis, there is no declarative illocutionary act found. This study covers various functions of illocutionary speech acts in the dialogue of the animated film Adam and Iblis such as; guessing, estimating, explaining, accusing, forbidding, persuading, praying, fearing, promising and swearing. Assertive illocutionary speech acts are the dominant type of illocutionary speech acts used in the Devil's dialogue in the animated film Adam and Iblis.